Computerized tomographic findings of complex partial seizures in childhood and adolescence - Anlar, Banu; Renda, Yavuz; Erzen, Canan (The Turkish Journal of Pediatrics, 1987)
The CT findings of forty children and adolescents with complex partial seizures were evaluated in relation to the type of seizure, the EEG pattern and the response to therapy. The rate of CT abnormalities was 65%, the majority being atrophic changes. The patients who had unilateral temporal discharges on EEG, a definite or suspected cause for epilepsy, or refractory seizures were more likely to have abnormal scans. We believe that a CT is particularly indicated in these patient groups.
Keywords: computerized tomography; epilepsy; complex partial seizures